ANALYSIS OF THE COORDINATION OF THE 20 KV SYSTEM PROTECTION ON THE 30 MVA 150/20 KV TOWN FEEDER TRANSFORMER AT THE 150KV SURALAYA SUBSTATION - Kajat Sartono; Martin Djamin; Suryadi Suryadi (LPPM YPITI, 2026)
One type of protective relay that requires coordination in an electric power system is the overcurrent relay (OCR) and ground fault relay (GFR). The OCR/GFR function is crucial for protecting equipment in a substation from short circuits between phases or phase-to-ground faults. Therefore, setting the OCR/GFR relay requires careful and precise calculations to ensure a sensitive, selective, fast, and reliable power protection system. Observations of faults at several substations in the Cilegon Technical Implementation Unit (UPT) revealed discrepancies in the OCR/GFR coordination. The method used was to calculate the OCR/GFR setting values on the feeder side and the main transformer side to analyze the protection system coordination.